Parliament and parliamentarism: a comparative history of a European concept (European conceptual history) - Ihalainen, Pasi; Ilie, Cornelia; Palonen, Kari (Berghahn Books, 2016)
Parliamentary theory, practices, discourses, and institutions constitute a distinctively European contribution to modern politics. Taking a broad historical perspective, this cross-disciplinary, innovative, and rigorous collection locates the essence of parliamentarism in four key aspects-deliberation, representation, responsibility, and sovereignty-and explores the different ways in which they have been contested, reshaped, and implemented in a series of representative national and regional case studies. As one of the first comparative studies in conceptual history, this volume focuses on debates about the nature of parliament and parliamentarism within and across different European countries, representative institutions, and genres of political discourse.